2008
DOI: 10.1007/bf03195611
|View full text |Cite
|
Sign up to set email alerts
|

Practical application of daughter yield deviations in dairy cattle breeding

Abstract: Daughter yield deviations (DYDs) of bulls and yield deviations (YDs) of cows, besides estimated breeding values (EBVs), are standard measures of animals' genetic merits in routine genetic evaluations worldwide. In this contribution, we first point out differences and similarities between DYDs and EBVs calculated for milk, fat and protein yields. While the latter measure represents the additive polygenic value of an animal, the former consists of both the additive polygenic and residual components. Then, a summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…However, this seems inadequate when sire effects have to be predicted both on intercept and slope, where there is extra information from the performance of daughters across the range of the environmental descriptor. Szyda et al (2008) found that reliability of DYD in a random regression test-day model was dependent on the number of test-days per daughter as well as the number of daughters per son. The average number of test-days per daughter in our study was 6.19, whereas Szyda et al (2008) found that a minimum of 6 was needed to get reliable DYD.…”
Section: Discussionmentioning
confidence: 98%
“…However, this seems inadequate when sire effects have to be predicted both on intercept and slope, where there is extra information from the performance of daughters across the range of the environmental descriptor. Szyda et al (2008) found that reliability of DYD in a random regression test-day model was dependent on the number of test-days per daughter as well as the number of daughters per son. The average number of test-days per daughter in our study was 6.19, whereas Szyda et al (2008) found that a minimum of 6 was needed to get reliable DYD.…”
Section: Discussionmentioning
confidence: 98%
“…The effect of the studied locus depends on the genetic background of the animal and could differ between populations 43, 65. The BLUP, REML and Bayesian analysis methods incorporate common fixed effects for particular loci and ‘residual’ random effects of remaining polygenes to provide more exact results 7, 43, 45. Another approach for obtaining more exact results is also to use particular loci as random effects with IBD to account for their variability 8, 55…”
Section: Methods For Evaluating Genetic Markersmentioning
confidence: 99%
“…The total additive genetic variability is the sum of the known loci according to Eqn (5), adjusted for mutual linkages (7) and ‘residual’ additive genetic variability caused by the remaining polygene σ 2 Apol : Hence both single‐locus effects and the remaining polygenic effects of the ‘genetic background’ should be considered simultaneously 7, 42–45…”
Section: Genetically Conditioned Variability Of Performancementioning
confidence: 99%
See 1 more Smart Citation
“…However, progeny performances are often used as quasi-phenotype in reality as well. For example, in cattle breeding schemes, DYD are commonly employed, especially in the international genetic evaluation of bulls (Liu, Reinhardt, B€ unger, & Reents, 2004;Mrode & Swanson, 2004;Szyda, Ptak, Komisarek, & _ Zarnecki, 2008), where DYD is defined as the weighted average of a bull's daughter yields corrected for all fixed effects. Thus, we estimated prediction accuracy of GBV with Acc_N using DYD as phenotypic data in one of the simulated scenarios (cattle_2_Sel_VAL) to test the variety of weighting factors.…”
Section: Novel Approach Acc_n and Weighting Factor Xmentioning
confidence: 99%